2018
DOI: 10.1097/aog.0000000000002803
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bridge Contraception in Postpartum Long-Acting Reversible Contraception and Sterilization Fulfillment Rates

Abstract: Bridge contraception is associated with increased LARC and sterilization fulfillment after postpartum discharge. Long-acting reversible contraception or sterilization fulfillment after discharge occurred in less than one in four women. Strategies to improve provision of LARC or sterilization before hospital discharge are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
4
1
1
Order By: Relevance
“…A previous study showed that initiation of bridge contraception before obtaining interval LARC and sterilization was associated with increased interval LARC and sterilization fulfillment. 11 In our study, however, patients with PPLARC as a bridge were less likely to receive interval BTL despite ongoing desire. Again, for two of the patients interviewed, the PPLARC allowed they to continue to delay plan for PPBTL as they felt secure with the method.…”
Section: Discussioncontrasting
confidence: 53%
“…A previous study showed that initiation of bridge contraception before obtaining interval LARC and sterilization was associated with increased interval LARC and sterilization fulfillment. 11 In our study, however, patients with PPLARC as a bridge were less likely to receive interval BTL despite ongoing desire. Again, for two of the patients interviewed, the PPLARC allowed they to continue to delay plan for PPBTL as they felt secure with the method.…”
Section: Discussioncontrasting
confidence: 53%
“…A sample size of 198 participants was calculated, based on an estimated incidence of 47% (± 5%) contraception use at 90-days postpartum and an alpha of 0.05. 5,9 A random sample of 299 charts was reviewed to account for patients who would be excluded or lost to follow-up by 90 days. Each patient's chart was reviewed by one of six fourth-year medical students trained in chart abstraction.…”
Section: Methodsmentioning
confidence: 99%
“…In one study of over 8,000 postpartum women at a single institution, less than one in four women who expressed interest in LARCs at the time of hospital discharge successfully obtained one by 90 days postpartum. 9 States have been working to improve access to immediate postpartum contraception, including LARC. [10][11][12] In May 2018, a policy change was made for Kansas Medicaid to reimburse immediate postpartum LARC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggest that patient race, ethnicity, and socioeconomic status affect physician attitudes and practices around reversible contraception and permanent contraception, which raises concerns regarding differential counseling (26,27). For example, among patients with identical medical histories, patient race or ethnicity and socioeconomic status influenced recommendations for intrauterine contraception in ways that may reflect racial, ethnic, and social-class stereotypes (27)(28)(29).…”
Section: Longitudinalmentioning
confidence: 99%